2013
DOI: 10.1111/twec.12112
|View full text |Cite
|
Sign up to set email alerts
|

Political Risk, Institutions and Foreign Direct Investment: How Do They Relate in Various European Countries?

Abstract: This paper examines theoretically and empirically the extent to which the decision by foreign firms to invest in a group of countries is influenced by economic factors, as opposed to political risk and institutional performance. We consider the importance of these factors as drivers of foreign direct investment (FDI) for 32 European countries (subsequently divided into three pooled clusters) by means of panel regression techniques in two specifications over the 1995-2008 period. Our results suggest that risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…The macro aspects of risk are seen to emanate from the sudden changes in political system affecting capital and investment through all-out war, expropriation or civil unrest; while the micro part relates to the bureaucratic or administrative overloads, corruption and the inefficiencies found in the judiciary. The perspective given in the work of Benáček et al (2014) captured the basis for which MNEs reaction to host location characteristics take place. The study found that FDI going to receiving countries that are adjudge poor with weak and diverse institutions are found to be sensitive to political risk factors when compared to the one going to developed countries because of their long standing economies with similar institutional structure.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The macro aspects of risk are seen to emanate from the sudden changes in political system affecting capital and investment through all-out war, expropriation or civil unrest; while the micro part relates to the bureaucratic or administrative overloads, corruption and the inefficiencies found in the judiciary. The perspective given in the work of Benáček et al (2014) captured the basis for which MNEs reaction to host location characteristics take place. The study found that FDI going to receiving countries that are adjudge poor with weak and diverse institutions are found to be sensitive to political risk factors when compared to the one going to developed countries because of their long standing economies with similar institutional structure.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Insecurity may prevent trade even though it offers potential mutual gains [21,46] Inward FDI flows attract advanced foreign technology and innovative managerial skills. This, in turn, leads to a better distribution of CP support [47] Better IQ causes higher inward FDI flows forming a favourable environment and a flexible local government decision-making system [21,23,48,49] Territorial capital/ conditions…”
Section: Conditioning Factor Effect On Outcomes Of the Cp Relation Wimentioning
confidence: 99%
“…The paucity of research in the area is surprising in that a political environment that is viewed as stable and predictable is the basis of a county's ability to create a suitable environment that attracts investment (Benáček et al 2014;Bin et al 2004;Manzoor 2013). The Chinese stock market has suffered significant plunges since the outburst of the Global Financial Crisis and it has been kept afloat by massive state intervention.…”
Section: Has the Uk Political Instability Spilled-over To Chinese Stomentioning
confidence: 99%